An In Vitro Evaluation of Industrial Hemp Extracts Against the Phytopathogenic Bacteria Erwinia carotovora, Pseudomonas syringae pv. tomato, and Pseudomonas syringae pv. tabaci - Getrude G. Kanyairita; Desmond G. Mortley; Willard E. Collier; Sheritta Fagbodun; Jamila M. Mweta; Hilarie Uwamahoro; Le’Shaun T. Dowell; Mwamba F. Mukuka (Molecules)
Pests and diseases have caused significant problems since the domestication of crops, resulting in economic loss and hunger. To overcome these problems, synthetic pesticides were developed to control pests; however, there are significant detrimental side effects of synthetic pesticides on the environment and human health. There is an urgent need to develop safer and more sustainable pesticides. Industrial hemp is a reservoir of compounds that could potentially replace some synthetic bactericides, fungicides, and insecticides. We determined the efficacy of industrial hemp extracts against Pseudomonas syringae pv. tabaci (PSTA), Pseudomonas syringae pv. tomato (PSTO), and Erwinia carotovora (EC). The study revealed a minimum inhibitory concentration (MIC) of 2.05 mg/mL and a non-inhibitory concentration (NIC) of 1.2 mg/mL for PSTA, an MIC of 5.7 mg/mL and NIC of 0.66 mg/mL for PSTO, and an MIC of 12.04 mg/mL and NIC of 5.4 mg/mL for EC. Time-kill assays indicated the regrowth of E. carotovora at 4 × MIC after 15 h and P. syringae pv. tomato at 2 × MIC after 20 h; however, P. syringae pv. tabaci had no regrowth. The susceptibility of test bacteria to hemp extract can be ordered from the most susceptible to the least susceptible, as follows: P. syringae pv. tabaci > P. syringae pv. tomato > E. carotovora. Overall, the data indicate hemp extract is a potential source of sustainable and safe biopesticides against these major plant pathogens.